Responses of benthic algal communities and their traits to experimental changes in fine sediments, nutrients and flow. (21st June 2017) - Neif, Érika M.; Graeber, Daniel; Rodrigues, Liliana; Rosenhøj‐Leth, Simon; Jensen, Tinna M.; Wiberg‐Larsen, Peter; Landkildehus, Frank; Riis, Tenna; Baattrup‐Pedersen, Annette
Summary: Lowland stream ecosystems are subjected to multiple anthropogenic stressors, usually nutrient enrichment in combination with sedimentation of fine particles and low flow periods in summer. Here, we investigated the temporal development of the benthic algae community in response to these three stressors and linkages to the trait characteristics of the community to explore the mechanisms responsible for stress‐induced community changes. We investigated the response of benthic algae species composition, traits (life forms, cell size categories), biovolume and chlorophyll a (Chl‐ a ) concentration to low flow in combination with nutrient enrichment and fine sedimentation in twelve large outdoor stream flumes (12 m long) resembling small streams in size and habitat characteristics. The experiment consisted of two phases: a normal‐flow phase followed by a low‐flow phase (90% current velocity reduction), each spanning 4 weeks. We applied a eutrophication scenario (mean increases of 1.14–5.48 mg N/L and 0.01–0.06 mg P/L in the flumes for dissolved inorganic nitrogen and phosphate respectively) throughout the experiment. Under low flow, we supplemented this with a fine sedimentation scenario (>90% stream bed cover). We took samples once in the normal‐flow phase and every week during the low‐flow phase. We observed strong responses in the benthic algae community to sudden changes in low flow and fine sedimentation, mediating rapid species turnover with a decreased algal biovolume and increased abundance of large, motile species. However, we did not observe any pronounced responses to nutrient enrichment. In contrast to the observations for other variables, we found a continuous increase in Chl‐ a concentration during low flow. This was likely due to continuous fine sedimentation during this phase, reducing light availability which probably resulted in an increase of cell‐level Chl‐ a concentration in response to light limitation and lower rates of light‐induced Chl‐ a degradation. The rapid response of the benthic algal community to the applied stressors suggests that even short periods of major stressor exposure may significantly affect benthic algae in lowland systems. We suggest that short‐term stress events may have cascading effects on several important ecosystem processes given the importance of benthic algae for the productivity of these systems.